Effectiveness of Implementing Synchronous and Asynchronous Blended E-Learning in Stunting Prevention and Treatment Training Programs - Namira Sari, Indah; Dinn Wahyudin; Rusman (JTP - Jurnal Teknologi Pendidikan, 2023)
The Covid 19 pandemic has had such a big impact on the education system, especially the National education system. In the conditions of the Covid 19 pandemic, national learning is carried out online, both formal and non-formal education (training). Related to this, the authors conducted a study on the application of asynchronous and synchronous blended learning in Stunting Prevention and Handling Training held at the Ministry of Social education and training institutions. The purpose of this study is to find out the effectiveness and constraints of implementing asynchronous blended learning and synchronous training. The method used in this study is a literature study. The results of the study show that the implementation of asynchronous and synchronous blended online learning Training on Stunting Prevention and Handling is not yet effective. This is due to the asynchronous setting being carried out only with independent asynchronous (AM) without the presence of a facilitator. The existence of a facilitator can play an important role in maintaining and maintaining the level of student learning motivation and facilitating relationships between training participants and with the facilitator. Then in the implementation of synchronous online learning Training on Stunting Prevention and Handling is also considered less effective. The main obstacle is the internet network which is not accessible to participants, especially from remote areas. So that it is very difficult for participants to follow synchronous learning as a whole.